The impact of monetary policy on economic growth in Cambodia: Bayesian approach - Sean, Monorith (Journal of Management, Economics, and Industrial Organization, 2019)
This research paper aims to study the significance of monetary policy in the contribution to the economic growth of Cambodia. This study employs the data in the period of 2000-2018 consisting in total 19 years. Once the GDP of Cambodia is characterized as the limited dependent variable, the Tobit model is an appropriate model to be used. However, due to the limited data which only consists of 19 observations, this study uses Bayesian inference. The combination between Tobit model and Bayesian inference is known as Bayesian Tobit Model. The Bayesian Tobit Model with Markov chain Monte Carlo simulation uses Gibbs sampling to sample all conditional posterior distributions. The empirical results illustrate that money supply which represents the monetary policy tool is statistically indicated a positive correlation with GDP in Cambodia. Moreover, the inflation rate and exchange also revealed a positive relationship with GDP. The interest rate, on the other hand, is confirmed negatively insignificant with GDP which represents economic growth in Cambodia. Based on statistical results, the National Bank of Cambodia plays a vital role in authorizing the monetary policy in Cambodia.